2008
DOI: 10.1037/0893-3200.22.3.448
|View full text |Cite
|
Sign up to set email alerts
|

Family and individual difference predictors of trait aspects of negative interpersonal behaviors during emerging adulthood.

Abstract: A latent trait-state-occasion model (TSO; Cole, Martin, & Steiger, 2005) was used to isolate the trait and state components of negative interpersonal behaviors toward a friend or romantic partner during emerging adulthood. Results indicated that variance in negative interpersonal behaviors was due to nearly equal portions of trait and occasion factors. Variability in the trait aspects of negative interpersonal behaviors was then predicted by theoretically relevant constructs. In particular, mothers' negative b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 51 publications
2
16
0
1
Order By: Relevance
“…The results indicated that perceived parenting styles contribute to both emotional regulation and trait emotionality. In line with numerous studies, our results support the notion that interrelations exist between these three constructs over all developmental stages (Eisenberg et al, 2003;Fish, Stifter, & Belsky, 1991;Hatton et al, 2008). We predicted that when young adults report that their primary caregiver used an authoritative parenting style, they would also report positive emotion, while authoritarian and permissive parenting would predict high levels of negative emotion.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results indicated that perceived parenting styles contribute to both emotional regulation and trait emotionality. In line with numerous studies, our results support the notion that interrelations exist between these three constructs over all developmental stages (Eisenberg et al, 2003;Fish, Stifter, & Belsky, 1991;Hatton et al, 2008). We predicted that when young adults report that their primary caregiver used an authoritative parenting style, they would also report positive emotion, while authoritarian and permissive parenting would predict high levels of negative emotion.…”
Section: Discussionsupporting
confidence: 91%
“…Over all developmental periods, numerous studies demonstrate interrelations between parental responding and children's emotion (Eisenberg et al, 2003;Fish, Stifter, & Belsky, 1991;Hatton et al, 2008). Presenting one instructive finding, Yap and her colleagues (2011) showed that the ability to self-regulate in an effortful manner may be a protective factor buffering the higher likelihood of trait-negative people to develop depression.…”
mentioning
confidence: 99%
“…However, the loadings of Half1 relative to Half2 were similar to the average loadings of the items in a previous factor analysis of the DBRS (Friedman-Weieneth et al, 2009). This is not problematic, and other studies have allowed the loadings to vary (e.g., Hatton et al, 2008; Schaufeli, Maassen, Bakker, & Sixma, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Some environmental factors identified in previous studies, such as childhood stroke (Max et al, 2002), lead exposure (Nigg et al, 2010), traumatic brain injury (Yeates et al, 2005), low birth weight (Breslau et al, 1996; Groen-Blokhuis et al, 2011), and psychosocial factors such as a less-stimulating and supportive home environment (Sagiv et al, 2013), could contribute to this non-shared environmental trait variance. Future research could explore this by incorporating such potential risk factors into the TSO model, as predictors of the trait factor (as in Hatton et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…1 The emotions a person constantly experiences and expresses may either facilitate or impede his or her relationships with others (Didonato, Bedminster, & Machel, 2013;Hatton et al, 2008). When facing emotional events, similar emotions between two persons may provide shared knowledge and feeling of closeness, enhance perspective taking and empathy, and facilitate communication and solution.…”
Section: Emotional Reaction Tendenciesmentioning
confidence: 99%